Relation of Intima Media Thickening of Carotid Arteries with Parameters of Lipid Profile in Chronic Hepatitis C Patients - Talat Samreen; Asma Aijaz; Shazia Fahmi; Hira Ahmad; Nasreen Naz; Erum Amir (Journal of Bahria University Medical and Dental College)
Objective: To find out the relation between carotid intima media thickening (CIMT) and lipid profile in HCV seropositive patients. Study Design & Setting: Descriptive, cross sectional study. Methodology: Study was conducted in the Institute of Basic Medical Sciences of Dow University of Health Sciences. Duration of study wsd 13 months. After ethical approval, a total of ninety participants including thirty (n=30) control (Group A) and sixty (n=60) HCV sero-positive patients (Group B) were inducted in the study from the hepatitis clinic of Ruth Pfau Civil Hospital, Karachi, Those with history of smoking, hypertension, alcohol, pregnancy, ascities, coinfection with other hepatitis viruses and not willing to participate were excluded. After consent, demographic and anthropometric data were recorded. Blood samples were taken for fasting blood glucose and lipid profile estimation. CIMT was estimated by carotid doppler ultrasound. Data entered and analyzed by SPSS version 20.0. and presented as frequency (n; %) and mean ±SD. Student “t” test and Pearson’s correlation test were applied where appropriate. A p-value of <0.05 was considered as statistically significant. Results: Demographic and anthropometric characteristics of HCV sero-positive participants showed non-significant difference compared to control. FBG and CIMT were found to be significantly raised in HCV infected patients while lipid profile parameters showed insignificant difference. Pearson’s correlation test revealed insignificant relation of lipid profile parameters with CIMT (p > 0.000). Conclusion: HCV seropositive patients had significantly raised CIMT with non-significant relation with parameters of lipid profile.